The Effect of Perceived Organizational Support on Work Engagement Through Job Crafting (Study At General Division Employees Of Bank Jatim Head Office Surabaya) - Lady Oktafia Alfatekha W; Budiono (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
Bank Jatim or PT Bank Pembangunan Daerah Jawa Timur Tbk , on august 17, 1961 Bank Jatiwas establised in Surabaya. as a BUMD, Bank Jatim is the largest bank in East Java. The goal of this research is to examine and analyze the impact of employee’s perceived organizational support on work engagement through job crafting at the General Division in Bank Jatim Surabaya. This study is a causal research of quantitative approach. A total of 56 respondent are used for the sampling technique. With the support of SmartPLS v.3.6.2 software, the statistical analysis used in this research is Partial Least Square (PLS). The analysis outcomes indicate that perceived organizational support has a significant positive effect on work engagement, perceived organizational support has a significant positive effect on job crafting, job crafting has a significant positive effect on work engagement, and job crafting has successfully mediated the effect of perceived organizational support on work engagement.